Extension and advice: Animated information - Pittendrigh, Barry; Bello-Bravo, Julia; Seufferheld, Francisco (Technical Centre for Agricultural and Rural Cooperation, 2011)
Animations developed to be viewed on cell phones provide a unique way of delivering agricultural advice, as the short videos can be adapted for a variety of languages.